Numerical simulation of natural ventilation effectiveness in removing fire smoke at multi-storey car park / Muhammad Saifuddin Abdul Rahman, Azli Abd Razak and Qi Jie Kwong - Abdul Rahman, Muhammad Saifuddin; Abd Razak, Azli; Qi, Jie Kwong (UiTM Press, 2022)
Simulation study using Fire Dynamic Simulation (FDS) has been conducted on a simplified car park model. As this work aims to analyse the effectiveness of natural ventilation in the dissipation of smoke, all models’ dimensions and opening size corresponded to the Uniform Building by Law (UBBL) 1984 requirements, which allowed the models to be without any mechanical ventilation system or alarm. The fire source is produced by a modelled car located at the centre of the building at the rate of 4MW. This is to represent a possible case within a car park area. Focuses were placed on the heat and hazardous gases produced by the car. The result shows that designs with different parameters exhibited different natural ventilation results for temperature and visibility at a preset height of 2.5m. Another critical observation was made on the smoke concentration and temperature outputs, which concentrated on the opening and tight corners. This is due to the inability of the heat flow to be removed from the building via natural ventilation. Therefore, this study reasonably concludes the importance of opening size and fire position with this simulation results and data.